Sosialisasi Uang Layak Edar Kepada Masyarakat Desa Kadumekar Babakancikao Purwakarta - Jalaludin Jalaludin; Dede Indri (STIE Syariah Indonesia Purwakarta, 2026)
Based on the results of observations, the PKM team found several unique phenomena related to Decent Money among the Kadumekar Village Community, one of which is that there are still people who are taboo on decent money and not worthy of circulation, lack of access to adequate information related to decent money, Kadumekar Village with a population that mostly works as farmers and small traders, is very vulnerable to the problem of counterfeit or unfit money fraud, and the last phenomenon is that people understand culture more than government rules or policies. The purpose of this PKM is to socialize decent money to the people of Kadumekar Village, so that people understand the importance of using money that is valid and worthy of circulation. This PKM method uses observation, socialization and discussion, monitoring and evaluation. The conclusion of this PKM is that before the implementation of the socialization of decent money to the people of Kadumekar Village, the average value of respondents is 31.11 (very does not understand), and after this socialization activity is carried out, the average value of respondents is 90.55 (very understanding). This shows that socialization is important as a medium for education, including reminding people who once knew about money worthy of circulation and not worthy of circulation. In addition, after the implementation of this PKM, the community already knows the characteristics of money worthy of circulation and not worthy of circulation, the importance of recognizing money worthy of circulation and not worthy of circulation, the characteristics of money worthy of circulation and not worthy of circulation, the impact of use including the legal impact of money not worthy of circulation, and the community no longer uses damaged money for transactions, damaged money is exchanged to banking institutions.